STRATEGI PENGEMBANGAN USAHA TIM KOORDINASI PENANGGULANGAN KEMISKINAN (TKPK) DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI PEKANBARU - Fadel M. Azhari; Dadang Mashur (Cross-border, 2022)
Poverty in Riau Province is still quite high, this is caused by several factors from the phenomenon of poverty that occurs. One of the causes of the increase in the poverty rate in Riau Province is the impact of Covid-19 which has caused several phenomena such as increased unemployment, paralysis of the commercial sector due to low purchasing power of the people, inflation rate of basic needs and low quantity of goods needed. Besides the Covid-19 phenomenon, the cause of poverty in Pekanbaru is also due to the low level of Human Resources in Pekanbaru so that people are less effective in efforts to improve their welfare. TKPK in carrying out its work program, especially in business development for MSMEs, has a strategy for accelerating poverty reduction, namely business development and program synergy. TKPK is committed to overcoming the problem of poverty in Riau Province together with the relevant stakeholders to be able to carry out business development for MSMEs. This study used a purposive sampling technique with a qualitative research type with a descriptive approach, the required data such as primary data and secondary data were obtained through interviews and documentation and then analyzed based on research problems. The results of this study indicate that the TKPK's business development strategy did not work well, while the inhibiting factors of this strategy were the TKPK's commitment to carrying out its responsibilities and poor coordination between stakeholders.